Strategi Inovatif Mengatasi Kesulitan Belajar Siswa SMP: Perspektif Kognitif Piaget: Innovative Strategies to Overcome Learning Difficulties in Junior High School Students: A Piagetian Cognitive Perspective - Mulya, Zhia Ajrin; Putri, Indriani Kristanti Kurnia; Chadjijah, Sitti; Hariyanto, Teguh (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2024)
Students' learning difficulties remain a fundamental issue in the field of education, particularly in mathematics at the elementary and secondary school levels. This study aims to analyze the factors causing students’ learning difficulties based on Jean Piaget’s theory of cognitive development, and to explore effective strategies for addressing these issues through a holistic approach. The method employed in this research is a Systematic Literature Review (SLR), which is a structured and methodical approach to identifying, evaluating, and synthesizing previous relevant studies. The literature was purposively selected from various national and international academic journals published between 2014 and 2024. The findings reveal that the mismatch between teaching methods and students’ stages of cognitive development is the primary cause of learning obstacles. In addition, affective factors such as emotional intelligence and spiritual well-being significantly influence students’ motivation and participation in the learning process. The study also finds that students’ engagement in religious activities can strengthen character and reduce non-cognitive learning barriers. The conclusion emphasizes the importance of an integrative approach that considers both cognitive and affective aspects in designing effective learning strategies. The implication is that teachers need to thoroughly understand students’ developmental stages in order to implement appropriate, adaptive, and holistic instructional methods.